Novel Antiviral Activity of Ethyl 3-Hydroxyhexanoate Against Coxsackievirus B Infection - Olasunkanmi, Oluwatayo Israel; Mageto, James; Avala Ntsigouaye, Juval; Yi, Ming; Fei, Yanru; Chen, Yang; Chen, Sijia; Xu, Weizhen; Lin, Lexun; Zhao, Wenran; Wang, Yan; Zhong, Zhao-Hua (Frontiers in Microbiology, 2022)
Coxsackievirus group B (CVB) is a member of the genus Enterovirus in the family Picornaviridae. CVB infection has been implicated as a major etiologic agent of viral myocarditis, dilated cardiomyopathy, meningitis and pancreatitis among children and young adults. Until date, no antiviral agent has been licensed for the treatment of Coxsackievirus infection. In an effort to identify antiviral agents against diseases caused by the CVB, we found that ethyl 3-hydroxyhexanoate (EHX), a volatile compound present in fruits and food additives, is a potent antiviral compound. Herein, we demonstrated that EHX treatment significantly inhibits CVB replication both in vivo and in vitro.Furthermore, EHX possesses antiviral activity at effective concentration (EC50) of 1.2 µM and cytotoxicity (CC50) of 25.0 µM, yielding a selective index (SI) value as high as 20.8. Insights into the mechanism of antiviral activity of EHX showed that it acts at the step of viral RNA replication. Since EHX has received approval as food additives, treatment of CVB-related infections with EHX might be a safe therapeutic option and may be a promising strategy for the development of semi-synthetic antiviral drugs for emerging and re-emerging viral diseases.